Sequestrated lumbar disc herniation mimicking intradural spinal tumor: A case report: Disc herniation mimicking intradural tumor - Kızılay, Zahir; Sağıroğlu, Sinan; Kahraman Çetin, Nesibe; Çetiner, Melih; Yaycıoğlu, Soner (Journal of Surgery and Medicine, 2025)
Sequestered disc herniation is characterized by a portion of the nucleus pulposus rupturing and releasing into the spinal canal. The size of this extruded disc fragment can range from small to large. In certain instances, the disc fragment may be large enough to obstruct cerebrospinal circulation, causing it to be confused with intradural pathologies in radiological imaging. This confusion can potentially impact the choice of surgical approach for spinal interventions. This study presents and discusses a case of an atypically located sequestered disc herniation, initially misdiagnosed as an intradural tumor on radiological imaging.